Surgical strategies for recurrent hiatal hernia: three-point fundoplication fixation - Yuxiao Chu; Yanyang Liu; Rong Hua; Qiyuan Yao (BMC Surgery)
Abstract Background The management of a recurrent (symptomatic) hiatal hernia remains controversial. This study aimed to review the outcomes of patients who underwent recurrent repair of hiatal hernias. Methods Thirteen patients who underwent recurrent hiatal hernia repairs at our hospital between 2018 and 2024 were reviewed retrospectively. The postoperative outcomes and complications of these patients were investigated. Results Thirteen patients were included in this study. The median time of reoperation from the previous hiatal hernia repair was 3 years (IQR, 2.5–5). Patients with a history of only one repair accounted for 76.9%, whereas those with two repairs accounted for 23.1%. All reoperations were completed laparoscopically. No deaths or readmissions during the 30-day postoperative period were recorded at an average of 30.5 ± 20.9 (6–68) months of follow-up. No other complications or symptoms were recorded, and oral medication was discontinued in eleven (84.6%) patients. The average GERD-Q score was 6.7 ± 1.3 postoperatively, whereas it was 10.4 ± 3.0 preoperatively. Conclusion We present several surgical strategies for addressing the recurrence of hiatal hernias. The key is not only to accurately close the hernia ring but also to fix the fundoplication to reduce the impact on the tissue around the hiatus to reduce the incidence of recurrence. Our three-point fixation technique showed promising effects in preventing recurrence but needs further study. Clinical Trial Number ChiCTR2100049995.